Universal Design for Learning in Inclusive Kindergarten Education Across Urban, Suburban, and Remote Contexts in Indonesia - Saikhu, Ali; Hermanto, Hermanto (Journal of Innovation and Research in Primary Education, 2025)
Universal Design for Learning (UDL) represents a critical framework for creating inclusive educational environments, yet its implementation in early childhood education remains underexplored, particularly in developing countries. Contemporary early childhood institutions often evaluate children based on socially constructed notions of normalcy, potentially excluding diverse learners. This study investigates UDL implementation challenges and opportunities in inclusive kindergarten education across diverse geographical contexts. A qualitative multi-site case study was conducted across three kindergarten schools in East Kutai Regency, Indonesia, representing urban, suburban, and remote areas. Data were collected through structured interviews with six participants (principals and teachers), classroom observations, and document analysis. Analysis followed Edward III's policy implementation framework, examining communication, resources, disposition, and bureaucratic structure dimensions. All schools demonstrated positive attitudes toward UDL implementation and established communication mechanisms, though with varying effectiveness. Significant resource disparities existed across geographical contexts, with urban schools having better access to specialized personnel and infrastructure. The availability of only one Special Assistant Teacher for the entire regency highlighted severe resource constraints. Bureaucratic support varied substantially, with urban schools receiving more systematic institutional backing compared to suburban and remote areas. While positive educator attitudes provide implementation foundation, substantial gaps exist between intention and capacity. Resource inequalities and inconsistent institutional support perpetuate educational exclusion rather than promoting genuine inclusion. The findings reveal that effective UDL implementation requires coordinated systemic support addressing not only individual bias but also institutional policies that maintain exclusionary practices.